1977
DOI: 10.1073/pnas.74.8.3404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of colchicine on cyclic AMP levels in human leukocytes

Abstract: The increase in human leukocyte adenosine 3':5'-cyclic monophosphate (cyclic AMP) levels seen in response to various substances was markedly potentiated by colchicine and other agents that affect microtubule assembly. Addition of dI-isoproterenol (2 AiM) or prostaglandin El (10 ttM), together with the phosphodiesterase inhibitor isobutylmethylxanthine (1 mM), caused a much greater increase in cyclic AMP in colchicine-pretreated cells tan in control cells. With isoproterenol (2 MM) plus isobutylmethylxanthine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
1

Year Published

1978
1978
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(55 citation statements)
references
References 27 publications
4
49
1
1
Order By: Relevance
“…The intact cell procedure provides the possibility for investigating the ,8-adrenergic receptor system under physiological conditions, retaining the integrity of the cell and all factors which are required for B-adrenergic receptor function. This includes in particular soluble factors such as guanine nucleotides and functional cytoskeletal elements, which may be lost in membrane preparations (Ross et al, 1977;Rudolph et al, 1977). A change in these factors may have caused the observed differences between fl-adrenergic receptor affinity for agonists and antagonists in intact and broken cell preparations.…”
Section: Discussionmentioning
confidence: 99%
“…The intact cell procedure provides the possibility for investigating the ,8-adrenergic receptor system under physiological conditions, retaining the integrity of the cell and all factors which are required for B-adrenergic receptor function. This includes in particular soluble factors such as guanine nucleotides and functional cytoskeletal elements, which may be lost in membrane preparations (Ross et al, 1977;Rudolph et al, 1977). A change in these factors may have caused the observed differences between fl-adrenergic receptor affinity for agonists and antagonists in intact and broken cell preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, colchicine, by a microtubuledependent mechanism, enhances capping of concanavalin Abinding glycoproteins ( 10) but diminishes surface expression of receptors for TNFa (6), insulin (9), and /3-adrenergic agonists ( 11). Colchicine also inhibits assembly of the leukotreineB4-forming complex at the plasma membrane (5), affects the interactions of heterotrimeric G proteins with the catalytic subunit of adenylate cyclase (13), increases intracellular cAMP (14), and enhances the synthesis of stable prostaglandins (15). Each of these effects, shared with vinblastine and nocodazole but not lumicolchicine, has been held responsible for one or another of the effects of colchicine in inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…This extends a recent study which shows that disruption of microtubules in normal human !eukocytes potentiates cyclic AMP stimulation by various inducers [41 ]. However, by studying different types of leukemic cells, we have found that the inhibitory effect of intact microtubules on this hormonal stimulation was not universal for all cells, and seems to be associated with the general activity of cell surface microtubules.…”
Section: Discussionmentioning
confidence: 89%